2015
DOI: 10.1038/srep15139
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagram and Transformations of Iron Pentacarbonyl to nm Layered Hematite and Carbon-Oxygen Polymer under Pressure

Abstract: We present the phase diagram of Fe(CO)5, consisting of three molecular polymorphs (phase I, II and III) and an extended polymeric phase that can be recovered at ambient condition. The phase diagram indicates a limited stability of Fe(CO)5 within a pressure-temperature dome formed below the liquid- phase II- polymer triple point at 4.2 GPa and 580 K. The limited stability, in turn, signifies the temperature-induced weakening of Fe-CO back bonds, which eventually leads to the dissociation of Fe-CO at the onset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In literature, Raman spectrum of α-Fe 2 O 3 shows similar characteristic phonon modes, e.g., peak positions at 225 and 495 cm −1 are attributed to the A 1g mode, whereas, peak at positions 245, 290, 406, 611 and 818 cm −1 are attributed as E g modes [7,16,17,24]. The peak at 1309 cm −1 is also associated with the α-Fe 2 O 3 particle [7,25]. Moreover, the origin of the peak at 659 cm −1 is still not clear and discrepancies exist in literature.…”
Section: Raman Spectroscopic Studiesmentioning
confidence: 71%
“…In literature, Raman spectrum of α-Fe 2 O 3 shows similar characteristic phonon modes, e.g., peak positions at 225 and 495 cm −1 are attributed to the A 1g mode, whereas, peak at positions 245, 290, 406, 611 and 818 cm −1 are attributed as E g modes [7,16,17,24]. The peak at 1309 cm −1 is also associated with the α-Fe 2 O 3 particle [7,25]. Moreover, the origin of the peak at 659 cm −1 is still not clear and discrepancies exist in literature.…”
Section: Raman Spectroscopic Studiesmentioning
confidence: 71%
“…Experiments performed at high pressures (GPa) on pure CO, produced a metastable CO polymer (Lipp et al, 2005 ) structurally characterized by partially interconnected polycarbonyl chains where the monomeric unit of five carbons contains a lactone moiety (Bernard et al, 1998 ). Further high pressure experiments conducted on Fe(CO) 5 resulted in a mixture of Fe 2 O 3 crystals immersed in a polymerized CO (Ryu et al, 2015 ). Overall, CO polymerization is a difficult reaction if a catalyst is not involved.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we have re-examined the structure and vibrational spectroscopy of Fe­(CO) 5 , both of which have provided surprises. The diffraction study found a hitherto unknown phase transition, although a recent study of iron carbonyl using Raman spectroscopy had determined that two high-pressure phases exist in the region up to ∼16 GPa and ∼600 K, above which pressures and temperatures the material breaks down into a mixture of hematite and a polymeric C−O solid. In that work, the I → II phase boundary was represented by a straight line with a zero-pressure intercept at ∼160 K; however, the scatter of their observations is consistent with a steeper d T /d P at low pressure that could result in an intercept closer to 100 K. It thus seems reasonable to hypothesize that the high-pressure phase II is the same as our low-temperature phase II.…”
Section: Discussionmentioning
confidence: 99%